Hubungan Boredom dengan Cyberslacking pada Mahasiswa - Syafiqah, Nurul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to see the relationship between boredom and cyberslacking in students at (UNP) Padang State University. This study applies a quantitative approach by involving Padang State University students as the population in the research and a total sample of 346 students determined through the cluster random sampling technique. Data was collected through questionnaires to measure cyberslacking and boredom based on the concept of cyberslacking. The analysis of the data was carried out by the Pearson Product Moment correlation test with the help of the SPSS 26 for Windows program. The results showed that in general, cyberslacking and boredom in students were in the medium category, with a Pearson correlation value of 0.684 for the variables of cyberslacking and boredom.